2009
DOI: 10.1037/a0015051
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of life satisfaction in the first 5 years following traumatic brain injury.

Abstract: Objectives:The trajectories of life satisfaction for 609 individuals who sustained a traumatic brain injury (TBI) were studied. Hierarchical linear modeling analysis examined individual level growth trends over the first 5 years following TBI using gender, functional independence, age, and time to estimate life satisfaction trajectories. Measures: Participants completed the Functional Independence Measure and the Life Satisfaction Inventory at years 1, 2, 4, and 5 after sustaining TBI. Results: Participants wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 52 publications
(55 reference statements)
4
50
4
Order By: Relevance
“…The mean LSI-A score, 13.18, was consistent with the mean scores of older adults reported elsewhere (11.67-19.33) (Cohen & Schemm, 2007;Neugarten et al, 1961;Resch et al, 2009). The mean PIL score, 115, was higher than in Crumbaugh and Maholick's normative sample of 805 adults, whose mean PIL score was 112.4, and higher than the Ebersole and Quiring sample 46 M. Troutman et al was greater than the means reported in other older adult samples-17.2 ; 17.9 (Pruchno, Burant, & Peters, 1997), and 18.37 (Kim, Kim, & Kim, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…The mean LSI-A score, 13.18, was consistent with the mean scores of older adults reported elsewhere (11.67-19.33) (Cohen & Schemm, 2007;Neugarten et al, 1961;Resch et al, 2009). The mean PIL score, 115, was higher than in Crumbaugh and Maholick's normative sample of 805 adults, whose mean PIL score was 112.4, and higher than the Ebersole and Quiring sample 46 M. Troutman et al was greater than the means reported in other older adult samples-17.2 ; 17.9 (Pruchno, Burant, & Peters, 1997), and 18.37 (Kim, Kim, & Kim, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…and .97) with TBI populations and to be sensitive to changes in functional ability from admission to discharge and follow-up [14][15][16][17].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Approximately 1.5 million people in America sustain a TBI each year and nearly 100,000 of these patients have permanent physical, cognitive, and or behavioral disabilities (Resch, Villarreal, Johnson, Elliott, & Kwok, 2009 ).Young children are particularly vulnerable to the injury event itself and to ongoing problems (Hessen, Nestvold, & Anderson, 2007 ;McKinlay, Dalrymple-Alford, Horwood, & Fergusson, 2002 ;McKinlay, Grace, Horwood, Fergusson, & MacFarlane, 2009 ). The heterogeneity and complexity of the impairments and injury itself compound the diffi culties that patients experience (Maas, Stocchetti, & Bullock, 2008 ); however, little is known about how the general public perceive individuals who have experienced a TBI.…”
Section: Introductionmentioning
confidence: 98%